Closed Mitral Commissurotomy (CMC) at Bangabandhu Sheikh Mujib Medical University - Outcome Study - Rahman, Zerzina; Nuruzzaman, Mostafa; Ahsan, Nazib; Sultana, Ayesha; Hoque, Rezwanul; Hossain, Aslam (University Heart Journal, 2011)
Mitral stenosis (MS) occurs nearly exclusively as a consequence of rheumatic fever. The rheumatic process evokes the inflammatory changes in the valve endothelium resulting in narrowing of the orifice. Depending upon the severity of the disease, the treatment modality varies and the choice may be either Percutaneous transluminal mitral commissurotomy (PTMC), Closed mitral commissurotomy (CMC), Open mitral commissurotomy or valvuloplasty (OMC) or straight a way mitral valve replacement (MVR) procedure. In this observational study the results of 25 CMC operations done from February ‘09 through September ’09 is presented. A review of results of CMC operations done abroad is also presented. The outcome of this low cost operation for early cases of mitral stenosis is quite satisfactory. Keyword: Rheumatic valvular disease; Closed mitral commissurotomy; immediate outcome DOI: 10.3329/uhj.v6i2.7249 University Heart Journal Vol. 6, No. 2, July 2010 pp.78-81